Composição química da soja (Glicine max (L.) Merril) em conversão para agricultura orgânica considerando as condições climáticas do oeste do Paraná - Justen, Gisele Cristina (2007)
The objective of this work was to compare the chemical composition of the soy in conversion for organic agriculture - 1° year in conversion (C1), 2° year in conversion (C2) and 3° year in organic conversion or (C3) - being known the data meteorological of the culture place. To cultivate used it was the CD-216, proceeding from harvest 2005/2006, the City of Santa Helena/PR. The studied variables had been the text of humidity and the centesimal composition (protein, oil, ashes and carbohydrates), the mineral text (P, K, Ca, Mg, Zn, Cu, Fe and Mn) and the text of isoflavones of the grains. Considering the three years in conversion, some factors had differed significantly. The text of humidity in C1 (8,43 %) differed significantly from C2 (9,04 %). For leached ashes and oil texts significant difference between the three years was observed. The raised texts more of oil (21,1 %) and leached ashes (4,79%) had been found in C3. It did not have significant differences between the treatments for the text of protein and carbohydrates, however the biggest texts had been found in C1. In relation to minerals, the studied components had occurred significant differences between all, to the exception of the N. The concentrations of P, K and Cu had been significantly bigger in C1. The concentrations of Mg in C1 and C2 had been similar, differing significantly in C3. The concentrations of Ca, Zn and Mn had been significantly bigger in C3. The concentration of Fe was significantly bigger in C2. The text of total isoflavones differed significantly between C1, C2 and C3, being superior in C3. Isoflavones Daidzina, Genistina and Malonil-Genistina had demonstrated significant differences between the years in conversion. These isoflavones had also presented greaters texts in C3. Isoflavones Malonil-Daidzina, Daidzeína, Genisteína had also presented expressives values in C3, however they had not differed significantly